Conservation Status of Lontar Palm Trees (Borassus flabellifer Linn) In Jeneponto District, South Sulawesi, Indonesia - Sirajuddin, Sukamaluddin; Mulyadi, Mulyadi; Dirawan, Gufran D.; Amir, Faizal; Pertiwi, Nurlita (Department of Agronomy and Horticulture, IPB University, 2016)
This study aimed to describe the botanical description, conservation status and potentials of Sulawesi native lontar palm trees (Barassus flabellifer Linn) in Jeneponto district, South Sulawesi, Indonesia. This study was extended to include a study on the community’s attitude towards preservation of lontar palm trees involving 30 people distributed over three research sites. Overall 53% of the dry-land in Jeneponto district is grown by lontar palm trees with the tree density ranging from 50 trees per ha for trees aged between 1-5 years; 37 trees per ha for trees aged between 5-10 years; and 32 trees per ha for trees aged more than 10 years. New lontar palm trees which are being managed by the local communities are planted on 27% of the land area. Tamalatea sub- district has the largest lontar palm tree population in Jeneponto District.